Transradial access in acute myocardial infarction complicated by cardiogenic shock: Stratified analysis by shock severity. Issue 7 (3rd August 2020) - Tehrani, Behnam N.; Damluji, Abdulla A.; Sherwood, Matthew W.; Rosner, Carolyn; Truesdell, Alexander G.; Epps, Kelly C.; Howard, Edward; Barnett, Scott D.; Raja, Anika; deFilippi, Christopher R.; Murphy, Charles E.; O'Connor, Christopher M.; et al.
Abstract: Background: Transradial access (TRA) is associated with improved survival and reduced vascular complications in acute myocardial infarction (AMI). Limited data exist regarding TRA utilization and outcomes for AMI complicated by cardiogenic shock (CS). We sought to assess the safety, feasibility, and clinical outcomes of TRA in AMI‐CS. Methods: One‐hundred and fifty‐three patients with AMI‐CS were stratified into tertiles of disease severity using the CardShock score. The primary endpoint was successful percutaneous coronary intervention (PCI), defined as Thrombolysis in Myocardial Infarction III flow with survival to 30 days. Results: Mean age was 66 years, 72% were men, and 47% had diabetes. TRA was the preferred access site in patients with low and intermediate disease severity. Overall, 50 (32%) patients experienced major adverse cardiac and cerebrovascular events; most events (78%) occurred in patients undergoing transfemoral access (TFA) in the intermediate‐high tertiles of CS severity. Of the 41 (27%) total bleeding events, 32% occurred at the coronary angiography access site, of which 92% were in the TFA group. The use of ultrasound (US) guidance for TFA resulted in reduced coronary access‐site bleeding (8.5 vs. 33.0%, p = .01). In a hierarchical logistic regression model, utilizing TRA did not result in lower odds of successful PCI (Odds ratio [OR]: 1.36; 95% confidence interval [CI]: 0.54–3.40). Conclusion: This study suggests that TRA is feasible across the entire spectrum of AMI‐CS and is associated with reduced coronary access‐site bleeding. In addition, US‐guided TFA is associated with reductions in access‐site bleeding and vascular complications. Concerted efforts should be made to incorporate vascular access protocols into existing CS algorithms in dedicated shock care centers.